Intelligent Three Lane Traffic Light System Using Raspberry Pi - H. Shree Kumar, Dr. A. Jagadeeshwaran, M. Shantha Kumar, Dr. Vijay Shankar, Mr. V.M Periyasmay (International Journal of Advanced Science and Technology, 2020)
Traffic over-crowding is one of the critical problem in urban areas due to incompetent traffic management system. The existing traffic system has a prima disadvantage of fixed countdown timer. The traffic rate is not same for all the lanes that is one lane may have ample number of vehicles and necessarily more green signal time while the other lane with less number of vehicles needs less time. The proposed system is a dynamical traffic light controller using raspberry pi which is based on number of vehicles in a lane. The signal timing of contrasting lanes will be different based on vehicle density in a particular lane. The proposed system acquiring the image of first lane and process it to observe vehicles in the particular lane using Haar Cascade method. According to the number of vehicles detected, the timing of the green signal for the same lane is set. This process is locomote by the next camera in the second lane and the process continuously circles depending upon the number of lanes. With the use of raspberry pi, the system will function using multiple number wireless device with bonded wireless network.